2010
DOI: 10.1007/s10585-010-9355-7
|View full text |Cite
|
Sign up to set email alerts
|

High levels of microRNA-21 in the stroma of colorectal cancers predict short disease-free survival in stage II colon cancer patients

Abstract: Approximately 25% of all patients with stage II colorectal cancer will experience recurrent disease and subsequently die within 5 years. MicroRNA-21 (miR-21) is upregulated in several cancer types and has been associated with survival in colon cancer. In the present study we developed a robust in situ hybridization assay using high-affinity Locked Nucleic Acid (LNA) probes that specifically detect miR-21 in formalin-fixed paraffin embedded (FFPE) tissue samples. The expression of miR-21 was analyzed by in situ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

23
230
0
1

Year Published

2011
2011
2021
2021

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 250 publications
(255 citation statements)
references
References 50 publications
23
230
0
1
Order By: Relevance
“…The discrepancy may be due to the differences in location of tumor site or tumor histological subtype. In line with this statement, the association of poor survival and miR-21 over-expression was only documented in colon cancer (24,43), but not in rectal cancer (43). In addition, high expression of miR-21 was also detected in adenocarcinoma sub-type (24).…”
Section: Discussionsupporting
confidence: 52%
See 1 more Smart Citation
“…The discrepancy may be due to the differences in location of tumor site or tumor histological subtype. In line with this statement, the association of poor survival and miR-21 over-expression was only documented in colon cancer (24,43), but not in rectal cancer (43). In addition, high expression of miR-21 was also detected in adenocarcinoma sub-type (24).…”
Section: Discussionsupporting
confidence: 52%
“…Due to the limited number of cases, we could not ascertain its expression in relation to tumor site and histological subtype. Interestingly, Nielsen et al observed that the expression of miR-21 was predominantly found in fibroblast-like cells located in the stromal compartment of the colon tumors (43). The cellular context of the tumors analyzed may also contribute to the discrepancy.…”
Section: Discussionmentioning
confidence: 99%
“…miRNA-21-5p was previously reported to show increased expression in tumor compared with normal colon mucosa (37), and was linked to early onset carcinogenesis (38). Two independent manuscripts reported that increased expression of miR21, predominantly in the stroma compartment and not the cancer cells, is associated with clinical outcome in TNM stage II colon cancer patients (39,40). These findings might explain why we did not see an association between miR21 expression and metastasis risk, unlike others (24).…”
Section: Discussionmentioning
confidence: 53%
“…We and others have implemented similar in situ hybridization (ISH) methods to identify the cellular compartment(s) of altered miRNA expression in a variety of solid tumors, including brain, breast, colorectal, lung, pancreatic, and prostate cancer (Dillhoff et al, 2008;Donnem et al, 2011;Gupta & Mo, 2011;Habbe et al, 2009;Jorgensen et al, 2010;Liu et al, 2010a;Nelson et al, 2006Nelson et al, , 2010Nelson & Wilfred, 2009;Nielsen et al, 2011;Preis et al, 2011;Qian et al, 2011;Rask et al, 2011;Schepeler et al, 2008;Schneider et al, 2011;Sempere et al, 2007Sempere et al, , 2010Yamamichi et al, 2009). miR-21 and miR-155 are frequently detected at higher levels in solid tumors and their differential expression correlates with outcome (Barbarotto et al, 2008;Sempere, 2011).…”
Section: Characterization Of Mirna Expression At Single Cell Resolutimentioning
confidence: 99%